CYCLIN B1 EXPRESSION IN MOTHERS OF DOWN SYNDROME VERSUS EUPLOID CHILDREN - Fabian Layton Tovar, Cristian; Consuelo Hinojosa Juárez, Araceli; Garduño Alanís, Adriana; Adriana Pérez González, Edith; Mendieta Zerón, Hugo (International Journal of Scientific Pediatrics, 2024)
Introduction. Down Syndrome (DS) is the most common chromosomopathy. Cyclin B1 is a regulatory protein involved in mitosis. The aim was to determine the cyclin B1 relative expression in mothers of DS patients. Methods. In this cross-sectional study, mononuclear cells of peripheral blood were obtained from 40 mothers of confirmed DS patients and 40 mothers of euploid patients, between 2019-2021. Demographic variables and cyclin B1 messenger RNA (mRNA) with real-time polymerase chain reaction (qPCR) were analyzed. The cases of DS mothers were compared to the relative expression of euploid group. Results. cyclin B1 mean relative expression by RT-PCR showed a significant difference between the group of mothers of DS children and mothers of euploid children (p < 0.05). The expression of the cyclin B1 was lower than the mean of mothers with euploid patients. Previously, it has been reported that the cyclin B1 down expression should accelerate telomere shortening in DS patients. Therefore, it would be advisable to recategorize the maternal age-related risk factor. Conclusion. Cyclin B1 may be a cost-effective biomarker in reproductive age women to present a DS case not associated with chronological age.